Hemostasis during Extreme Exertion - Kicken, Cécile Hélène; Miszta, Adam; Kelchtermans, Hilde; De Laat, Bas (Seminars in Thrombosis and Hemostasis, 2018)
Exercise is protective against cardiovascular disease, but can also provoke sudden cardiac death, a phenomenon referred to as “the exercise paradox.” Extreme exertion is known to induce a rebalanced hemostatic state by causing hypercoagulability and concomitantly enhanced fibrinolysis. Over the past decade, novel techniques for quantifying hemostasis have been introduced, which may provide new insights into this process. This review summarizes recent literature on the effect of extreme exertion of both short and long duration on coagulation, fibrinolysis, and recovery of hemostatic balance. Extreme exertion introduces a temporary hypercoagulable state, mainly through upregulation of the contact pathway by increased FVIII levels. Additionally, von Willebrand factor levels and platelet activation are increased. Simultaneously, increased fibrinolysis results from increased tissue-type plasminogen activator levels, suggesting a rebalanced hemostasis. The vascular endothelium appears to play a pivotal role in both processes. Data on the effect of exercise on endogenous anticoagulants are scarce. Hypercoagulability persists for hours to a day after prolonged extreme exertion, while fibrinolytic parameters appear to return to baseline levels more quickly. Hence, the balance in the rebalanced hemostatic state may be lost during recovery. Training induces lower amplitude of the hypercoagulable response, and quicker recuperation toward baseline. Repetitive exercise exhausts the endothelium, attenuating procoagulant changes. Additional research is needed to identify if the hemostatic balance is lost during recovery, and if so, when the shift toward thrombosis appears. Moreover, differences between sexes need to be addressed, since women are known to have a different pathophysiological mechanism behind cardiovascular events, but are underrepresented in recent literature.
Keywords: exercise; thrombosis; hemostasis; platelet function; fibrinolysis